A Novel Dissection Method of the Internal Mammary (Thoracic) Artery: Anastomotic Vessel of the DIEP Flap - Shigeki Sakai, MD, PhD; Ikki Yuzaki, MD; Hayato Nagashima, MD, PhD; Hiroki Kajita, MD; Tomoki Kiuchi, MD; Naohiro Ishii, MD, PhD; Kyoichi Matsuzaki, MD, PhD; Yoshifumi Takatsume, PhD; Kazuo Kishi, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. Deep inferior epigastric perforator flaps are commonly used for breast reconstruction using autologous tissue. For such free flaps, the internal mammary artery provides stable blood flow as the recipient for anastomosis. We report a novel dissection method of the internal mammary artery. First, the perichondrium and costal cartilage of the sternocostal joint are dissected with electrocautery. Then, the incision on the perichondrium is extended along the cephalic and caudal ends. Next, this C-shaped superficial layer of perichondrium is elevated from the cartilage. The cartilage is incompletely fractured with electrocautery, with the deep layer of perichondrium intact. Then, the cartilage is completely fractured by leverage and removed. The remaining deep layer of perichondrium is incised at the costochondral junction and shifted aside, revealing the internal mammary artery. The preserved perichondrium creates a rabbet joint to protect the anastomosed artery. This method not only enables a more reliable, safer dissection of the internal mammary artery, but also allows reusage of the perichondrium as underlayment in the setting of anastomosis, and coverage for the incised rib edge, protecting the anastomosed vessels.